Manajemen Kantor di Era Digital: Adaptasi dan Inovasi Sumber Daya Manusia dalam Transformasi Digital - Asfari, Urfi; Prayuda, Rifky Gilang (International Journal Administration, Business & Organization, 2025)
The advancement of digital technology has transformed traditional office management into a digital-based model, demanding organizations to adapt in terms of efficiency, productivity, and competitiveness Previous studies have primarily focused on technical aspects such as document digitization and information systems leaving a significant gap in understanding how human resources (HR) and strategic innovation respond to digital disruption. This article aims to analyze adaptation strategies and innovation in digital office management, emphasizing the integration of technology, human resource development, and data-driven policy formulation. The research method used is a critical literature review of prior studies. The findings reveal that successful digital transformation depends not only on technology adoption but also on organizational culture readiness, change management, and adaptive leadership. This article contributes by integrating human and strategic perspectives to tackle digital challenges, offering practical recommendations for both professionals and academics in optimizing office management during the Fourth Industrial Revolution.